2013
DOI: 10.3892/ijo.2013.1963
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA-200 family targets multiple non-small cell lung cancer prognostic markers in H1299 cells and BEAS-2B cells

Abstract: Lung cancer remains the leading cause of cancer-related mortality for both men and women. Tumor recurrence and metastasis is the major cause of lung cancer treatment failure and death. The microRNA-200 (miR-200) family is a powerful regulator of the epithelial-mesenchymal transition (EMT) process, which is essential in tumor metastasis. Nevertheless, miR-200 family target genes that promote metastasis in non-small cell lung cancer (NSCLC) remain largely unknown. Here, we sought to investigate whether the micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
81
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 60 publications
2
81
0
Order By: Relevance
“…In support of this theory, a previous study by Valastyan et al had shown that alteration of miR-31 modulated multiple target genes and affected multiple phenotypes, such as motility, invasion, and resistance to anoikis (Valastyan et al, 2009). Pacurari M et al reported the miR-200 family and these potential targets were functionally involved in canonical pathways of immune response, molecular mechanisms of cancer, metastasis signaling, cell-cell communication, proliferation and DNA repair in Ingenuity pathway analysis (Pacurari et al, 2013). Multiple-to-multiple relationships between miRNAs and targets have been reported by transfection experiments involving human gastric cancer cells (Hashimoto et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this theory, a previous study by Valastyan et al had shown that alteration of miR-31 modulated multiple target genes and affected multiple phenotypes, such as motility, invasion, and resistance to anoikis (Valastyan et al, 2009). Pacurari M et al reported the miR-200 family and these potential targets were functionally involved in canonical pathways of immune response, molecular mechanisms of cancer, metastasis signaling, cell-cell communication, proliferation and DNA repair in Ingenuity pathway analysis (Pacurari et al, 2013). Multiple-to-multiple relationships between miRNAs and targets have been reported by transfection experiments involving human gastric cancer cells (Hashimoto et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of markers has been studied or is under investigation in NSCLC in order to thoroughly understand disease progression (26,(41)(42)(43). EMT is one of the pathways for NSCLC progression.…”
Section: Discussionmentioning
confidence: 99%
“…This can occur via a perfect complimentary binding of the miRNA to the target mRNA (endonucleolytic cleavage of the mRNA) or by an imperfect complimentary binding to the target mRNA (translation repression). 32 Due to their cell cycle interference, miRNAs are involved either as oncogenes or as oncosuppressors in the pathogenesis of a huge variety of human cancers such as lung cancer, 33,34 prostate cancer, 35 colorectal cancer, 36,37 leukemia, [38][39][40] gliomas 41 and medulloblastoma, 42 diffuse large B-cell lymphoma, 43 hepatocellular carcinoma (HCC), 44 gastric cancer, 45,46 osteosarcoma, 47 renal cell carcinoma, 48 BC, 49 and OC. 50 Particularly, their presence in the blood has been shown to be associated with histology, clinical stage, survival, and oncogenic expression in OC and BC.…”
Section: Introductionmentioning
confidence: 99%